Sosialisasi Kelestarian Lingkungan Di Taman Kanak-Kanak Al-Aziziyah Desa Mideuen Jok Kecamatan Samalanga Bireuen - Junaidi Junaidi; Syarkawi Syarkawi; Eliana Eliana; Siti Nurhaliza (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2023)
This socialization of environmental sustainability activities is carried out to increase students' understanding of protecting the environment. This activity is carried out to guide students in caring for their environment. This activity was carried out during the teaching and learning process at Al-Aziziyah Samalanga Kindergarten. Socialization of environmental sustainability is one of the activities needed in kindergarten besides training students to protect the environment and also to care for the nature that surrounds them.